Primary hydatid cyst in the adductor magnus muscle - Özdemir, Meltem (BJR Case Rep, 2020)
Human hydatid cyst is a zoonotic disease caused by the larvae of the Echinococcus species, most commonly the Echinococcus granulosus. Although hydatid cyst can cause disease almost anywhere in the human body, it most commonly affects the liver and lungs. Primary musculoskeletal hydatid involvement is a very rare occurrence even in endemic regions. Musculoskeletal hydatid disease shows no pathognomonic clinical signs and symptoms. And the contribution of serology to the diagnosis is negligible due to the high rate of false-negative results. Therefore, radiological imaging studies have a critical role in the diagnosis of the disease. To the best of our knowledge, there are only a few case reports of primary hydatid involvement of the adductor magnus muscle in the current literature. Here we present a 55-year-old female patient with primary hydatid cyst in the adductor magnus muscle and discuss the case in terms of imaging.